Pendekatan Realistic Mathematics Education (RME) pada Mata Kuliah Bilangan Mahasiswa Program Studi PGSD - Ismi Widyaningrum; Ratna Dewi; Linda Linda; Asep Saefullah Kamali; Ajeng Muliasari (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
This study aims to find out the impact of the Realistic Mathematics Education (RME) approach on Pendidikan Guru Sekolah Dasar (PGSD) student learning outcomes on number courses, academic year 2023/2024. In this study two cycles were perfomed, cycle I and cycle II, where at the end of each cycle a test was given. In the cycle I, learning is done using conventional methods or teachers-centric learning. In the cycle II, learning with RME approaches. From both of these cycles, it is concluded that the learning outcomes in the cycle II have improved from the cycles I, this means that learning with the RME approach has higher results than learning with conventional method.